DAKWAH DI ERA POST-TRUTH: MENGELOLA DISINFORMASI DALAM KOMUNIKASI ISLAM - Novri Rivaldi Chandra Putra; Winda Kustiawan; Tubagus Rizki Hardinasyah; Fakhrur Rozi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
The post-truth era is characterized by the dominance of emotions and personal beliefs over objective facts in the shaping of public opinion. This phenomenon presents significant challenges for Islamic *da'wah* (preaching), particularly in addressing the rampant spread of disinformation on social media. This article examines the implications of the post-truth era for *da'wah* communication, the phenomenon of disinformation within an Islamic context, and strategies for managing it. Employing a qualitative approach—specifically through literature review and critical analysis—the article aims to provide insights for *da'is* (preachers) and Islamic institutions on establishing relevant and effective *da'wah* communication in the digital age.